Temporal order judgements of dynamic gaze stimuli reveal a postdictive prioritisation of averted over direct shifts - Binetti, Nicola; Harrison, Charlotte; Mareschal, Isabelle; Johnston, Alan (SAGE Publications, 2017)
We studied temporal order judgements (TOJs) of gaze shift behaviours and evaluated the impact of gaze direction (direct and averted gaze) and face context information (both eyes set within a single face or each eye within two adjacent hemifaces) on TOJ performance measures. Avatar faces initially gazed leftwards or rightwards (Starting Gaze Direction). This was followed by sequential and independent left and right eye gaze shifts with various amounts of stimulus onset asynchrony. Gaze shifts could be either Matching (both eyes end up pointing direct or averted) or Mismatching (one eye ends up pointing direct, the other averted). Matching shifts revealed an attentional cueing mechanism, where TOJs were biased in favour of the eye lying in the hemispace cued by the avatar’s Starting Gaze Direction. For example, the left eye was more likely to be judged as shifting first when the avatar initially gazed toward the left side of the screen. Mismatching shifts showed biased TOJs in favour of the eye performing the averted shift, but only in the context of two separate hemifaces that does not violate expectations of directional gaze shift congruency. This suggests a postdictive inferential strategy that prioritises eye movements based on the type of gaze shift, independently of where attention is initially allocated. Averted shifts are prioritised over direct, as these might signal the presence of behaviourally relevant information in the environment.